STRATEGI DAKWAH INTERAKTIF MELALUI PLATFORM DIGITAL: STUDI KASUS PENGGUNAAN KOMPUTER OLEH GENERASI Z - R Nurhayati; Syamsir, Syamsir; Rismawati , Rismawati; Ningsih , Diarti Andra (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2025)
This study aims to examine interactive da'wah strategies through digital platforms utilizing computers, specifically in the context of Generation Z, who are highly familiar with technology. This research employs a library research method by collecting and analyzing various literature sources related to digital da'wah, the characteristics of Generation Z, and computer-based communication media. The findings indicate that Generation Z prefers interactive da'wah, which is relevant to their daily lives and creatively presented through various digital platforms. The success of digital da'wah is determined by three main aspects: interactivity, content relevance, and creativity in presentation. Therefore, preachers need to master digital literacy and optimize the use of computers so that da'wah messages can be delivered effectively in this digital era.